2015
DOI: 10.1007/s13524-014-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Married Individuals Learning HIV Status in Malawi: Divorce, Number of Sexual Partners, and Condom Use With Spouses

Abstract: This article assesses how married individuals’ knowledge of HIV status gained through HIV testing and counseling (HTC) affects divorce, the number of sexual partners, and the use of condoms within marriage. This study improves upon previous studies on this topic because the randomized incentives affecting the propensity to be tested for HIV permit control for selective testing. Instrumental variable probit and linear models are estimated, using a randomized experiment administered as part of the Malawi Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…In addition, sex education implementing positive information, such as preventive (e.g., risk avoidance) and protective behaviors (e.g., STIs protection), may have a great impact on adolescent sexual health. In fact, one study showed that receiving correct information enhanced individuals' protective actions against future risky behaviors [128]. However, given the sensitive nature of these topics, before school officials and parents aim to cultivate adolescents' media literacy or provide sex-related information, confidentiality between the two parties must be established [129].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex education implementing positive information, such as preventive (e.g., risk avoidance) and protective behaviors (e.g., STIs protection), may have a great impact on adolescent sexual health. In fact, one study showed that receiving correct information enhanced individuals' protective actions against future risky behaviors [128]. However, given the sensitive nature of these topics, before school officials and parents aim to cultivate adolescents' media literacy or provide sex-related information, confidentiality between the two parties must be established [129].…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania couple counseling and testing services are well implemented and accessible in various levels of the health facilities. In SSA, couple counseling and testing services are known to improve adoption of safer sex practices including condom use and reduction of multiple sexual partners among couples [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They usually contain information on respondents’ reported marriages, including marriage dates and how unions ended. Researchers have previously used survey-based marriage histories to calculate the probabilities of divorce and remarriage, examine the sociodemographic factors associated with these events, and identify respondents who divorced and/or remarried between survey waves ( Amoateng and Heaton 1989 ; Anglewicz and Reniers 2014 ; Boileau et al 2009 ; Brandon 1990 ; Fedor, Kohler, and Behrman 2015 ; Gage-Brandon 1992 ; Grant and Yeatman 2014 ; Hampshire and Randall 2000 ; Locoh and Thiriat 1995 ; Reniers 2003 , 2008 ; Reniers and Tfaily 2008 ; Takyi and Gyimah 2007 ; Tilson and Larsen 2000 ). Despite their value, retrospective marriage histories, like other forms of survey data, may be incomplete or contain incorrect information.…”
Section: Introductionmentioning
confidence: 99%